2013
DOI: 10.3389/fendo.2013.00030
|View full text |Cite
|
Sign up to set email alerts
|

Selective Use of Peri-Operative Steroids in Pituitary Tumor Surgery: Escape from Dogma

Abstract: Objective: Traditional neurosurgical practice calls for administration of peri-operative stress-dose steroids for sellar-suprasellar masses undergoing operative treatment. This practice is considered critical to prevent peri-operative complications associated with hypoadrenalism, such as hypotension and circulatory collapse. However, stress-dose steroids complicate the management of these patients. It has been our routine practice to use stress steroids during surgery only if the patient has clinical or bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…For the early postoperative incidence of adrenal insufficiency, we briefly summarized the morbidity of adrenal insufficiency in the preoperative HPAA integrated patients( Table 2 ) for the absence of RCT. There were 12 studies meeting our inclusion criteria[ 4 , 5 , 8 , 9 , 13 – 18 , 20 , 21 ]. The morbidity of early postoperative adrenal insufficiency ranged from 0.96% to 12.90%, with the overall morbidity of 5.55%(41/739).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the early postoperative incidence of adrenal insufficiency, we briefly summarized the morbidity of adrenal insufficiency in the preoperative HPAA integrated patients( Table 2 ) for the absence of RCT. There were 12 studies meeting our inclusion criteria[ 4 , 5 , 8 , 9 , 13 – 18 , 20 , 21 ]. The morbidity of early postoperative adrenal insufficiency ranged from 0.96% to 12.90%, with the overall morbidity of 5.55%(41/739).…”
Section: Resultsmentioning
confidence: 99%
“…The early postoperative diabetes insipidus was mentioned in 3 studies with 235 patients[ 5 , 9 , 19 , 20 ]. There was no significant difference of early postoperative diabetes insipidus in two groups, while the morbidity was 4 in no supplementation patients vs 12 in supplementation patients(P = 0.82).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Regan et al demonstrated that perioperative management without the use of any stress doses of steroid coverage results in no adverse events and is safe and beneficial in patients with a normal preoperative serum morning cortisol level who do not suffer from apoplexy. 19 The need for perioperative replacement therapy may be lower than was once thought. An excess of glucocorticoids leads to adverse clinical consequences, such as a reduced rate of tissue repair, decreased glucose tolerance, increased susceptibility to infection due to immune compromise, hypertension, gastric ulceration, weight gain, and aseptic necrosis of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…B. 100 mg Hydrocortison i. v. verabreicht wird [13,16,28,32,33] (Anmerkung: generell sind auch bei Hypophysenoperationen Glukokokortikoide intraoperativ in der Regel nicht zwingend notwendig, obwohl dies eine weit verbreitete Praxis ist). Am 1. postoperativen Tag sollte dann aber in der Früh unbedingt ein basaler Serum Cortisolwert (zur Evaluierung des operativen Erfolges bzw.…”
Section: Dfpunclassified